2021
DOI: 10.2147/ppa.s318030
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Patient-Reported Medication Adherence Instrument: Concerns Influencing Medication Adherence

Abstract: The purpose of this research was to conceptualize and develop a tool for identifying persons who are, or are likely to be, non-adherent to medications prescribed by their healthcare provider(s) by identifying concerns that patients have regarding their treatments. Patients and Methods: The target populations were persons diagnosed with atrial fibrillation or osteoarthritis, who were prescribed anticoagulants or over-the-counter or prescription pain medications, respectively. In this two-stage, multi-year, qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The authors found that fear of bleeding or other side effects and concerns about medication cost were the most frequently cited reasons for not refilling a prescription, representing an opportunity to better communicate the benefits and risks of OAC. 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found that fear of bleeding or other side effects and concerns about medication cost were the most frequently cited reasons for not refilling a prescription, representing an opportunity to better communicate the benefits and risks of OAC. 15 …”
Section: Discussionmentioning
confidence: 99%
“… 12 While adherence is frequently perceived as an issue of forgetfulness, studies show that unintentional and intentional nonadherence may be predicted by medication beliefs, financial barriers, education, economic circumstances, and sociodemographic factors. 13 , 14 , 15 More broadly, social determinants of health (SDoH) are defined as the “conditions in the environments where people are born, live, learn, work, play, worship, and age that affect a wide range of health, functioning, and quality‐of‐life outcomes and risks.” 16 SDoH associated with adverse health outcomes may also be associated with medication nonadherence. 17 Incremental increases in the number of an individual's social risk factors have been found to increase stroke risk in adults <75 years of age.…”
mentioning
confidence: 99%
“…For example, pre-operative patient expectations or patient activation, whereby compliant people may do other things that influence their outcomes after THA/TKA [ 15 , 70 ]. Surgeon factors that influence decisions regarding adherence [ 53 , 71 ], and the surgeon’s volume and surgical proficiency that may have more direct impacts on patient outcomes [ 72 ]. Different outcome measures and criteria used to determine compliance may yield different results.…”
Section: Discussionmentioning
confidence: 99%
“…We were interested to explore whether non-compliant VTE and antibiotic prophylaxis were associated with PROM after THA/TKA. Previous research has demonstrated that treatment adherence is associated with health outcomes, including patient satisfaction [53], quality of life [54], and nonadherence is associated with increased morbidity and costs [55]. Patients often lack clear understanding of their personal risk of VTE and SSI this may contribute to suboptimal levels of compliance with recommended prophylaxis [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…4 Multiple factors related to the patient (low health literacy, knowledge gaps, decreased cognition, unpleasant adverse reactions), provider (limited time, use of complex regimens, ineffective communication, mistrust), and the healthcare system (limited access to care, poor care coordination, insuffi cient insurance coverage, cost) may impact adherence to prescribed treatment plans. 2,[4][5][6] Patients may not understand the benefi ts of prescribed…”
mentioning
confidence: 99%